The effect of attending rehabilitation after traumatic knee joint injury on femoral articular cartilage morphology in collegiate rugby players with a history of intracapsular knee joint injury during two-year consecutive rugby seasons - Hori, Miyuki; Terada, Masafumi; Suga, Tadashi; Isaka, Tadao (Frontiers in Sports and Active Living, 2024)
Introduction This present study aimed to compare ultrasonographic measures of femoral articular cartilage during two-year seasons between collegiate rugby players who have attended supervised rehabilitation following intracapsular knee joint injury and those without a history of knee injury. Methods Using a prospective observational study design, 12 male collegiate rugby players with a previous history of intracapsular knee joint injury who have received and completed supervised rehabilitation following their injury and 44 players without knee joint injury participated in this study. Ultrasonographic images were used to verify changes in femoral articular cartilage thickness and cross-sectional area (CSA) with or without a previous history of knee joint injury over two consecutive rugby seasons. Results Significant time main effects were observed for the lateral condylar thickness (p < 0.001), the intercondylar thickness (p = 0.001), the medial condylar thickness (p < 0.001), and CSA (p < 0.001). No significant interactions nor group main effects were identified for all femoral articular cartilage (p < 0.05). Conclusions Collegiate rugby players demonstrated a decrease in femoral articular cartilage thickness and CSA over two-year consecutive rugby seasons. These findings indicate that engaging in collegiate rugby induces alterations in femoral articular cartilage structure. Furthermore, there were no differences in all femoral cartilage outcome measures between rugby players with and without a previous history of traumatic knee joint injury. Therefore, attending supervised rehabilitation at the time of their knee joint injury appeared to reduce the impact of a previous history of intracapsular knee joint injury on the change in femoral articular cartilage thickness and CSA among active rugby players.